Tantangan Berteologi Dan Bergereja Masa Kini - Firman Panjaitan (Sekolah Tinggi Teologi Moriah, 2022)
Theology is often not in line with the praxis of ministry in the church. As a result, theology is often separated from the church. This can happen, because theology in Indonesia inherits Western theology while churches in Indonesia develop according to their locus. Western theology, which often denies culture, is ultimately difficult to practice in church services, especially tribal (local) churches, which always take into account the cultural values that develop in the area. This needs to be addressed wisely, so that theology can practice with the ministry of the church. This article offers a way to be able to practice theology in the service life of churches in Indonesia by applying a cross-textual reading model or method in an effort to theology. Cross-textual reading is a way to understand the values of the Bible (way of theology) in the form of sacred texts with sacred texts in culture. There are efforts to accommodate theology, but in understanding the sacred texts of the Bible, it synergizes with cultural sacred texts, to create a culture-based church theology. If the biblical text speaks in parallel with cultural texts, then theology lives in line with the praxis of church ministry, and the theology that develops in Indonesian churches is theology rooted in Indonesian culture. Teologi seringkali tidak sejalan dengan praksis pelayanan di gereja. Akibatnya teologi seringkali terpisah dari gereja. Hal ini bisa terjadi, karena teologi di Indonesia mewarisi teologi Barat sedangkan gereja-gereja di Indonesia berkembang sesuai lokusnya. Teologi Barat, yang seringkali menafikan budaya, pada akhirnya sulit untuk berpraksis dalam pelayanan gereja, terkhusus gereja suku (lokal), yang selalu memperhitungkan nilai-nilai budaya yang berkembang dalam daerah tersebut. Hal ini perlu untuk disikapi dengan bijak, agar teologi dapat berpraksis dengan pelayanan gereja. Artikel ini menawarkan sebuah jalan untuk dapat mempraksiskan teologi dalam kehidupan pelayanan gereja-gereja di Indonesia dengan cara menerapkan model atau metode pembacaan lintas tekstual dalam upaya berteologi. Pembacaan lintas tekstual merupakan cara untuk memahami nilai-nilai Alkitab (cara berteologi) yang berupa teks suci dengan teks-teks suci dalam budaya. Ada upaya mengakomodasi teologi, tetapi dalam pemahaman teks suci Alkitab bersinergi dengan teks suci budaya, untuk menciptakan teologi gereja yang berbasiskan budaya. Jika teks Alkitab berbicara dalam kesejajaran dengan teks budaya, maka teologi hidup sejalan dengan praksis pelayanan gereja, dan teologi yang berkembang di gereja-gereja Indonesia adalah teologi yang mengakar pada budaya Indonesia.